LOGISTICS CORPORATE STRUCTURES SUPPLY CHAIN FINANCING EXPERIENCE OF DEVELOPED COUNTRIES - Makhmudov Samariddin Bakhriddinovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article covers the technological development of the logistics industry in developed countries, globalization and expected and growing demands of consumers. Logistics company corporate structures are designed to optimize supply chain efficiency, reduce costs, and improve customer service. In addition, important aspects of supply chain financing that enable smooth operations and mitigate financial risks are explained.